The clash : U.S.-Japanese relations throughout history - LaFeber, Walter (New York : W.W. Norton, 1998)
'When Commodore Matthew Perry sailed into Tokyo harbor in July 1853, opening Japan to the West, Americans and Japanese immediately began to clash with each other. For the past century, this clash has focused especially on which nation would take the lead in developing China's economic potential. The relationship between the United States and Japan and the competition over China remain immensely important, highly explosive, and little understood on either side of the Pacific.''Walter LaFeber, one of America's leading historians, has written the first book to tell the entire story. Using a full array of American and Japanese sources, LaFeber provides the history to understand these long-rooted differences, bringing us to the present-day tensions in U.S.-Japanese trade talks, the vicissitudes of rearming Japan, Japan's continuing importance in financing America's huge deficit, and the looming economic shadow of China - not only the world's most populous century but certain to be the next economic superpower.'--Jacket.
Originally published: New York : W.W. Norton, c1997.
Includes bibliographical references (pages 461-480) and index.
Keywords: United States -- Foreign relations -- Japan; Japan -- Foreign relations -- United States